Understanding psychological flexibility: A multimethod exploration of pursuing valued goals despite the presence of distress - Kashdan, Todd B; Disabato, David J; Goodman, Fallon R; Doorley, James D; McKnight, Patrick E (Psychological assessment, 2020)
Psychological flexibility (PF), defined as the ability to pursue valued life aims despite the presence of distress, is a fundamental contributor to health (Kashdan & Rottenberg, 2010). Existing measures of PF have failed to consider the valued goals that give context for why people are willing to manage distress. Using 4 independent samples and 3 follow-up samples, we examined the role of PF in well-being, emotional experience and regulation, resilience, goal pursuit, and daily functioning. We describe the development and psychometric properties of the Personalized Psychological Flexibility Index (PPFI), which captures tendencies to avoid, accept, and harness discomfort during valued goal pursuit. Correlational, laboratory, and experience-sampling methods show that the PPFI measures a trait-like individual difference dimension that is related to a variety of well-being and healthy personality constructs. Unlike existing measures of PF, the PPFI was shown to be distinct from negative emotionality. Beyond trait measures, the PPFI is associated with effective daily goals and life strivings pursuit and adaptive emotional and regulatory responses to stressful life events. By adopting our measurement index, PF may be better integrated into mainstream theory and research on adaptive human functioning. (PsycInfo Database Record (c) 2020 APA, all rights reserved).